Preface (English) - Panieri, Giuliana; Poto, Margherita Paola; Bertolotto Bianc, Giuliano (Septentrio Educational, 2023)
Introductory remarks: A collaboration between the projects Akma2 Ocean Senses and ECO_CARE leaves no one behind within the umbrella of the Agenda 2030.